The Impact of Information Quality and Transaction Security in Building Customer Trust in Mobile Banking Byond Bank Syariah Indonesia KCP Stabat - Assyifa, Hikmah; Febriyanni, Rani; Munte, Siti Nurhasanah; Islami, Syahwaliya; Dio, Muhammad (Yayasan Rahmat Islamiyah, 2025)
This study aims to determine the extent to which the quality of information and transaction security in the BYOND Mobile application influence customer trust, particularly at Bank Syariah Indonesia's Stabat Branch Office (KCP). Mobile banking services have become increasingly important in the digital age as they provide customers with convenience in conducting financial transactions. However, not all customers immediately trust this service. Therefore, this study employs a qualitative method using interview and observation techniques with users of the BYOND Mobile application. Data was collected from several customers with diverse backgrounds to ensure the research findings accurately reflect real-world conditions. The results indicate that the information provided through the application is considered clear, easy to understand, and comprehensive. The application's simple interface makes it easy for users to locate important features. In terms of security, the use of PINs, OTPs, and biometric features makes customers feel safe when conducting transactions.